ANALISIS PENGGUNAAN MEDIA VIDEO ANIMASI TERHADAP MOTIVASI BELAJAR SISWA DI SEKOLAH DASAR - Tia Irawan; Taufiqulloh Dahlan; Fina Fitrianisah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2021)
Motivation has an important role in learning activities. To foster learning motivation, learning can be done using learning media. One of the learning media that can increase students' learning motivation is animated video media. The purpose of this study is to describe: 1) The concept of using animated video media on student motivation in elementary school, 2) Analyzing the application of animated video media so that elementary school students' learning motivation increases, 3) The relationship between animated video learning media and elementary school students' learning motivation. This research uses descriptive qualitative analysis with the type of literature study research. The data sources used are primary and secondary data obtained from various sources of journals, books, theses, and other sources that support animated video media on student motivation in elementary school. The learning steps are carried out with the planning, implementation, observation, and evaluation stages. The results showed that animated video media can increase students' learning motivation because animated video media can provide broad insight to students in building their own knowledge, learning is not monotonous, and students understand abstract material into concrete.